FREEDOM OF RELIGION: Historical Review of Islam - M. Salaman (Khazanah: Jurnal Sejarah dan Kebudayaan Islam, 2018)
This paper wants to describe and analyze religious freedom in the view of Islam and in the trajectory of Islamic history. Whereas the approach used is a historical and descriptive analytical approach. The Islamic view of freedom of religion is to give freedom to a person to choose, carry out and exchange thoughts in religious matters, whether done with religionists or followers of other religions, whether in public or separate places, whether done alone or with other people. And when someone has declared himself to enter Islam he is obliged to carry out the teachings of Islam as a whole. In Islamic history, from the time of the Prophet Muhammad, al-Khulafa 'al-Rashidin, the Umayyads and the Abbasids, they gave religious freedom to anyone and any party and coexisted together to build civilization at that time.